2013
DOI: 10.1017/s1355617712001270
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Learning in Specific Language Impairment: Effects of Sequence Complexity

Abstract: According to the procedural deficit hypothesis (PDH), abnormal development in the procedural memory system could account for the language deficits observed in specific language impairment (SLI). Recent studies have supported this hypothesis by using a serial reaction time (SRT) task, during which a slower learning rate is observed in children with SLI compared to controls. Recently, we obtained contrasting results, demonstrating that children with SLI were able to learn a sequence as quickly and as accurately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 32 publications
2
47
0
5
Order By: Relevance
“…A better performance by children in a non-linguistic task compared to a linguistic task has already been reported in a study by Gabriel et al (2013). By studying procedural learning across visual and verbal modalities, the authors showed that all the children (with and without SLI) in the study processed visual stimuli more quickly than auditory stimuli.…”
Section: Impact Of Auditory Processingsupporting
confidence: 61%
“…A better performance by children in a non-linguistic task compared to a linguistic task has already been reported in a study by Gabriel et al (2013). By studying procedural learning across visual and verbal modalities, the authors showed that all the children (with and without SLI) in the study processed visual stimuli more quickly than auditory stimuli.…”
Section: Impact Of Auditory Processingsupporting
confidence: 61%
“…However, the same results regarding poor procedural learning in SLI have not been found in other studies (Gabriel et al, 2011, 2012; Lum & Bleses, 2012; Mayor-Dubois et al, 2012). Gabriel and her colleagues (2013) recently showed that their initial negative findings could have been due to the level of complexity of the sequences used in the studies. When more complex sequences were used in the SRT task, group effects did emerge (Gabriel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Procedural learning plays an important role in the child's early acquisitions, and deficits in this domain are thought to be at the origin of neurodevelopmental disorders such as specific language impairment (SLI) and developmental coordination disorder (DCD). Whereas many studies now explore the hypothesis of a link between impaired language or motor development and procedural learning deficits by studying clinical populations (Gabriel et al, 2013;Gabriel, Maillart, Guillaume, Stefaniak, & Meulemans, 2011;Gabriel, Stefaniak, Maillart, Schmitz, & Meulemans, 2012;Gheysen, Van Waelvelde, & Fias, 2011;Hedenius et al, 2011;Kémeny & Lukács, 2010;Lejeune, Catale, Willems, & Meulemans, 2013;Lum & Blese, 2012;Lum, Conti-Ramsden, Morgan, & Ullman, 2014;Lum, Conti-Ramsden, Page, & Ullman, 2011;Lum, Gelgic, & Conti-Ramsden, 2010; Mayor-Dubois, Van der Linden, Zesiger, & Roulet-Perez, 2012;Tomblin, Mainela-Arnold, & Zhang, 2007), it appears necessary to better define procedural learning abilities in typically developing children.…”
mentioning
confidence: 99%